Pengaruh Minuman Kunyit Asam Terhadap Intensitas Nyeri Haid (Dismenore) Pada Remaja Putri - Wahyuni, Sri (Coping: Community of Publishing in Nursing; Vol 2 No 2 (2014): JURNAL EDISI MEI-AGUSTUS 2014, 2014)
Normal 0 false false false EN-US X-NONE X-NONE Dysmenorrhea is the most common complaint that causing female adolescent absenteism in school and other activities. The content of curcumin in turmeric has been proven to have anti-inflammatory effects. Prostaglandin is produced when inflammatory mediators that causes pain during menstruation. Turmeric acid is a drinking made from turmeric. This study aims to determine the effect of turmeric acid drinking on the intensity of menstrual pain in female adolescent at SMA Negeri 5 Denpasar. This study is a pre-experimental (one group pretest and posttest design). Sample consisted of 30 female adolescent selected using purposive sampling method. The results prove that the changing in the intensity of menstrual pain in female adolescent after being given turmeric acid drinking ie 63.33% mild pain, moderate pain 33.3%, and 3.3% severe pain where the previous 73.3% moderate pain and 26.7% severe pain. Wilcoxon test was performed to get the sig 0.000 which means P <0.05, indicated that the turmeric acid drinking has an influence on the intensity of menstrual pain (dysmenorrhea). Based on the above findings, turmeric acid drinking can be suggested as pain relieve during menstrual period /* Style Definitions */ table.MsoNormalTable {mso-style-name:"Table Normal"; mso-tstyle-rowband-size:0; mso-tstyle-colband-size:0; mso-style-noshow:yes; mso-style-priority:99; mso-style-qformat:yes; mso-style-parent:""; mso-padding-alt:0in 5.4pt 0in 5.4pt; mso-para-margin:0in; mso-para-margin-bottom:.0001pt; text-align:justify; line-height:200%; mso-pagination:widow-orphan; font-size:11.0pt; font-family:"Calibri","sans-serif"; mso-ascii-font-family:Calibri; mso-ascii-theme-font:minor-latin; mso-fareast-font-family:"Times New Roman"; mso-fareast-theme-font:minor-fareast; mso-hansi-font-family:Calibri; mso-hansi-theme-font:minor-latin;}
Keywords: Turmeric Acid Drinking, Curcumin, dysmenorrhea, female adolescent.